加入世贸组织对中国计量器具市场结构的影响 = Impacts of WTO accession on the market structure of China's measurement equipment industry - 谭 立 Tan, Li (2008)
The purpose of this dissertation are to compare world development treads of measurement equipment industry with those in China to identify the problems in China’s measurement equipment industry and to recommend policy options for sound development of the industry.